The Influence of Innovation Behavior on Entrepreneurial Leadership through Dynamic Capabilities - Saryadi Saryadi; Liss Dyah Dewi Arini; Istiyawati Rahayu (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Entrepreneurial leadership has become a crucial competency in higher education institutions seeking to adapt to rapid environmental changes and increasing global competition. This study explores how innovation behavior and dynamic capabilities among lecturers contribute to fostering entrepreneurial leadership within universities. Specifically, it investigates the mediating role of dynamic capabilities in the relationship between innovation behaviour and entrepreneurial leadership. Using a quantitative research design, data were collected through a cross-sectional survey of 85 lecturers at Universitas Duta Bangsa Surakarta. Path analysis and the Sobel test were used to examine both direct and indirect effects. The results reveal that innovation behaviour significantly influences both dynamic capabilities and entrepreneurial leadership. Moreover, dynamic capabilities partially mediate the relationship between innovation behaviour and entrepreneurial leadership, highlighting their strategic role in enhancing institutional adaptability and innovation. These findings underscore the importance of cultivating innovation behaviour and developing dynamic capabilities among academic staff to promote entrepreneurial leadership. This research provides theoretical, managerial, and policy implications for university governance, emphasizing the need for supportive environments that encourage innovation and continuous development of academic competencies